2017
DOI: 10.1634/theoncologist.2016-0233
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoepidemiology of Clinically Relevant Hypothyroidism and Hypertension from Sunitinib and Sorafenib

Abstract: Background. Thyroid dysfunction and hypertension (HTN) have been sporadically reported with sunitinib (SUN) and sorafenib (SOR). Determination of the side effect incidence will enhance monitoring and management recommendations.Methods. An observational cohort study was performed using deidentified pharmacy claims data from a 3-year period to evaluate patients prescribed SUN, SOR, or capecitabine (CAP; comparison group). The primary outcome was time to first prescription for thyroid replacement or HTN treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…19 Our findings were consistent with those reported by Walko C.M. et al 20 who found that sunitinib and sorafenib remarkably increased the risk of clinically relevant hypothyroidism; the risk was reported to be at least four times higher with sunitinib than with sorafenib. A meta-analysis indicated that sunitinib, axitinib and cediranib remarkably increased the risk of allgrade hypothyroidism.…”
Section: Discussionsupporting
confidence: 92%
“…19 Our findings were consistent with those reported by Walko C.M. et al 20 who found that sunitinib and sorafenib remarkably increased the risk of clinically relevant hypothyroidism; the risk was reported to be at least four times higher with sunitinib than with sorafenib. A meta-analysis indicated that sunitinib, axitinib and cediranib remarkably increased the risk of allgrade hypothyroidism.…”
Section: Discussionsupporting
confidence: 92%
“…The synergistic antitumor effect of aspirin combined with sorafenib provides several advantages for clinical HCC patients: first, through combining with aspirin, the sensitivity of sorafenib is increased. Sorafenib, with its gifted and unique advantages in HCC, can benefit the increasing number of HCC patients that were originally sorafenib resistant; second, since there is a subgroup of HCC patients who suffer from deleterious side effects of sorafenib, after an initial satisfactory response, who then have to reduce the drug dosage or even terminate the therapy . With combination treatment, aspirin ameliorates the side effects of sorafenib, allowing more patients who could not tolerate sorafenib previously to re‐gain the benefits; third, sorafenib is an expensive oral medicine, it costs about $US 4,079 per month and about $US 40,639 ± $US 3,052 over a patient's lifetime according to research by Carr et al .…”
Section: Discussionmentioning
confidence: 99%
“…RCT, randomized controlled trial; non-RCTs, non-randomized con-trolled studies, CI, confidence interval. 23,24 physicians ought to be able to anticipate sunitinib-related TRAEs, and schedule modifications could improve the health-related quality of life of the patients. 19 While no direct comparison can be made between trials, a 2/1 schedule was associated with less toxicity, and consequently fewer patients required dose reductions, which could be beneficial for patient adherence by reducing treatment-related AEs and maintaining dose intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the incidences of thrombocytopenia and neutropenia showed only a reduced tendency for a 2/1 schedule, but was statistically significant when the data were confined to Grade 3 and 4 TRAEs. Considering individual TRAEs have a distinct timing of onset, 23 24 physicians ought to be able to anticipate sunitinib-related TRAEs, and schedule modifications could improve the health-related quality of life of the patients. 19 …”
Section: Discussionmentioning
confidence: 99%